Surviving the flood: the case of indigenous Batek of Malaysia - Sharifah Zahhura Syed Abdullah,; Rozieyati Mohamed Saleh,; Nur Haslindawaty Abdul Rashid,; Siti Hawa Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In Kelantan, the occurrence of flood is common, but a massive tsunami-like flood due to the receipt of high-density rain in Hulu Kelantan which happened on the 24th December 2014 was an exceptional event. Among the victims were the traditional semi-nomadic indigenous Batek who practice hunting, gathering and farming small plot of plants for their own consumption. To date, no data are yet available regarding the exact impact of this flood to their living conditions. As such, this study highlighted the coping strategies employed by the Batek people to survive this catastrophic flood, since they had never experienced any disaster events, neither naturally nor related to any unsustainable development activities. This study was carried out through qualitative approach utilizing focus group discussion. All the transcripts were coded and grouped by the themes that emerged from comparing shared characteristics and meanings using the software package for handling qualitative data, NVivo 10. The findings revealed that most of the participants believed that deforestation for the agricultural activity caused this massive flood. They had to build raft from bamboo to save themselves and other important things such as their personal documents. They survived for four days up on a hill with wild food sources such as ‘umbut bayas’, wild tubers and wild shoots before receiving basic needs from the relief teams. Data and information generated from this study can be used to provide a true understanding on the surviving strategies practiced during flooding on remote settlements, such as in the case of this Orang Asli Batek community. This is imperative so that in the future a more effective and systematic flood management can be provided in timely manner.